Regulation of interferon alpha production by the MAGUK-family protein CASK under H5N1 infection - Huang, Jing-Ying; Sung, Pei-Shan; Hsieh, Shie-Liang (Frontiers in Immunology, 2025)
CASK, a MAGUK family scaffold protein, regulates gene expression as a transcription co-activator in neurons. However, the mechanism of CASK nucleus translocation and the regulatory function of CASK in myeloid cells remains unclear. Here, we investigated its role in H5N1-infected macrophages. We found that H5N1 triggers CASK nuclear translocation via PKR and SRC signaling. HCK, a SRC family kinase, enhances CASK phosphorylation at S395 via CDK5, facilitating CASK’s nuclear entry. Knocking out CASK in myeloid cells specifically reduces interferon-alpha (IFNA) production by hindering the nuclear export of Ifna mRNA, while leaving its mRNA levels unchanged. Myeloid-specific CASK knockout (KO) mice display exacerbated lung inflammation, which correlates with reduced IFNA levels during H5N1 infection. Interactome studies show that H5N1 triggers associations between CASK and CCT4, STIP1, and TNK1. These associations recruit IRF7, POLR2C, TAF15, HNRNPs, and CRM1, enabling the CASK complex to bind to the Ifna promoter, bind co-transcriptionally to Ifna mRNA, and facilitate CRM1-dependent Ifna mRNA export. This underscores CASK’s critical role in the antiviral response.